Kelayakan Usaha Home Industry Rengginang Eka Di Desa Sumberejo Kecamatan Mondokan Kabupaten Sragen - Sholekah, Dwi; Anwar, Muhammad Fathul; Retnaningsih, Nugraheni (Universitas Veteran Bangun Nusantara, 2022)
The purpose of this study was to determine the cost structure including fixed costs and variable costs, revenues, profits, profitability and business feasibility of the rengginang Eka industry in Sumberejo Village, Mondokan District, Sragen Regency. The basic methods used are qualitative and quantitative. The research area was taken purposively, namely in Sumberejo Village, Mondokan District, Sragen Regency. Respondents were taken using a purposive technique, while the respondents to be selected included the owner and 2 employees in the home industry of Rengginang Eka. The data used are primary data and secondary data. The total fixed costs incurred by the home industry rengginang Eka are Rp. 13,517, the total variable costs are Rp. 612,640, so the total costs incurred are Rp. 626,157. The total income of the Rengginang Eka home industry in February was Rp. 1,440,000 and earned a profit of Rp. 813,843. then for the profitability analysis of 129.97%. The results of the feasibility study show that the BEP breaks even if the product BEP is 41.31 kg and for the BEP the price is Rp. 429,484. then for the R/C ratio of 2.30 and for the B/C ratio of 1.30 it is classified as profitable and feasible to work on. And the results of the ROI of 101% show that the ROI is positive, so the home industry rengginang Eka is feasible to be developed.